Vaccination against Hepatitis B among health care workers in the Bamenda Health District: influence of knowledge and attitudes, Cameroon - Ngum, Anye Muriel; Laure, Sobngwi Joëlle; Tchetnya, Xavier; Tambe, Tabe Armstrong; Ngwayu, Claude Nkfusai; Wirsiy, Frankline Sevidzem; Atuhaire, Catherine; Cumber, Samuel Nambile (The Pan African Medical Journal, 2021)
Introduction: Hepatitis B virus (HBV) infection is one of the most serious occupational hazards faced by healthcare workers (HCW). This study aimed at assessing the influence of knowledge and attitudes of HCWs in the Bamenda Health District (BHD) on their vaccination status. Methods: This was a cross-sectional analytic study carried out in Bamenda health district, Cameroon. Random sampling method was used to select 10 private, 10 publics, and 4 confessional health facilities, from which 280 HCW were included in the study by convenience sampling. Data were analysed using Epi Info 7 and presented using tables, figures, and percentages. Results: The vaccination coverage among HCW in the BHD was found to be 13.9%. Healthcare workers who had no knowledge of the minimum number of doses for complete primary HBV vaccination were less likely to be vaccinated than those who had knowledge (p = 0.00). Healthcare workers who had been tested for HBsAg were more likely to be vaccinated than those who had not done the test (p = 0.00). Among HCW (90.7%) who knew they were more at risk of contracting HBV, 98.6% knew it can be prevented out of which 72.6% reported that vaccination is the most effective means of prevention; only 13.9% of HCW were vaccinated. Other factors could have influenced the vaccination status of HCW; high cost of the vaccine, lack of time for vaccination, negligence, and the non-availability of the vaccine. Conclusion: Awareness should be created among HCW and they should be encouraged to go for HBsAg screening and those who are negative should receive a full dose of HBV vaccine. Also, the vaccine should be subsidized and made available to all HCW in the BHD.
Keywords: Hepatitis; Vaccination; Knowledge; Attitudes; Health care workers; Bamenda Health District; Cameroon